An Eco-Critical Analysis of Selected Hadiths of Prophet Muhammad on Environmental Issues - Hadi, Saja Abdul Ameer (International Conference on Islamic Studies, 2025)
This study addresses the pressing issue of global environmental degradation by exploring the relevance of Islamic prophetic traditions to contemporary ecological ethics. The research aims to uncover how selected Hadiths of Prophet Muhammad provide guidance for sustainable living and environmental stewardship within the Islamic tradition. Adopting an eco-critical analytical method, the study examines Hadiths related to key environmental concerns, including water conservation, the sacredness of nature, ecological agriculture, animal welfare, moderation in consumption, and cleanliness. Through detailed textual analysis, supported by a thematic table of Hadiths and their eco-critical dimensions, the findings reveal a comprehensive Islamic environmental ethic rooted in the interconnectedness of all creation, the concept of human stewardship (amanah) over nature, and the prohibition of wastefulness (israf) and corruption (fasad) on earth. The results demonstrate that prophetic teachings offer timeless wisdom and practical strategies for addressing modern environmental challenges, encouraging an integrated approach that links religion, ethics, and ecological action. The study’s contribution lies in showing the potential of Islamic scripture to inform environmental awareness, inspire green policy-making, and promote eco-friendly lifestyles in Muslim societies while fostering interfaith dialogue on environmental care, thereby enriching the global discourse on sustainability